Peningkatan Kemampuan Peneliti Muda Universitas Tadulako Melalui Pelatihan Aplikasi Nvivo dan Lisrel Untuk Riset Bisnis - Sihar Tambun; Riris Rotua Sitorus; Netty Laura S; Imam Suryono (CV. Ulil Albab Corp, 2023)
The Community Service Program is carried out with the aim of increasing the competence of researchers in the Master of Management Study Program at Tadulako University, Palu. There are two competencies to be improved. First, competence in the field of qualitative research through the use of the NVivo software. Second, competence in the field of quantitative research through the use of Lisrel software for structural equation modeling research. The method used is a services learning approach by conducting lectures and workshops. The output of this community service program is an increase in the competence of the participants which consists of two competencies. First, increasing competence in the field of qualitative research through the use of the NVivo software. This competency includes the ability to input internal data and external data into NVivo, the ability to code internal data and external data, the ability to process data and produce coding visualization images, and the ability to draw conclusions from coding visualization images. Second, increasing competence in the field of quantitative research through the use of the Lisrel software. This competence includes the ability to solve the problem of confirmatory factor analysis by using the modification indices facility in the Lisrel software, the ability to solve the goodness of fit problem in the structural equation modeling research model, the ability to create syntax to test indirect effects using the Lisrel software, and the ability to read data processing output with using the Lisrel software.